Prussian Blue‐Derived Synthesis of Hollow Porous Iron Pyrite Nanoparticles as Platinum‐Free Counter Electrodes for Highly Efficient Dye‐Sensitized Solar Cells. Issue 54 (7th August 2017) - Chen, Jeffrey E.; Fan, Miao‐Syuan; Chen, Yen‐Lin; Deng, Yu‐Heng; Kim, Jung Ho; Alamri, Hatem R.; Alothman, Zeid A.; Yamauchi, Yusuke; Ho, Kuo‐Chuan; Wu, Kevin C.‐W.
Abstract: Invited for the cover of this issue is the group of Kuo‐Chuan Ho and Kevin C.‐W. Wu at the National Taiwan University. The image depicts the hollow porous iron pyrite nanoparticles which are deposited on the conducting substrate as the counter electrode (CE) in a dye‐sensitized solar cell (DSSC). Iron pyrite, with a hollow porous structure, offers a high surface area for the reduction of the triiodide ions. The DSSC directly converts the sunlight into electric power, which could power the flashlight without pollution. It is expected that the DSSC will emerge as a new class of low cost energy conversion device. Read the full text of the article at 10.1002/chem.201702687 . Abstract : " We decided to collaborate to demonstrate its enhanced efficiency in dye‐sensitized solar cells ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 13284 ff. (DOI:10.1002/chem.201702687 ).